In Times of “Chastity”: An Inquiry into Some Recent Developments in the Field of Perversion - Bunta, Aleš (Filozofski vestnik, 2022)
This essay is part of a project that has set out, as one of its primary objectives, to observe perversions as important indicators of broader changes and developments within society. Both of the momenta I follow in this study meet all the requirements for such an inquiry. The first development to be examined is what I will call the decline of pornography. At a time when all of society is increasingly becoming pornographic in so many ways, it sounds strange to talk about the decline of pornography. And yet pornography as a genre is, I believe, losing ground to something else – to a distinctly different system of unfolding sexuality and its economic exploitation. The second development to be discussed is the rise of masochism. In this context, I will analyse certain reports that show that, especially since the outbreak of the pandemic COVID-19, the number of people practicing masochistic “heavy play” has increased significantly. It appears that in a period when one would expect people to be dreaming of the lifting of restrictions, freedom, or whatever, many have chosen to undertake the cruel path of “servitude”. Eventually, I will show that these two developments are essentially connected, probably even consubstantial.